2009
DOI: 10.1021/jo901651h
|View full text |Cite
|
Sign up to set email alerts
|

Spacer-Dependent Folding and Aggregation of Oligocholates in SDS Micelles

Abstract: Insertion of flexible, 4-aminobutyroyl spacers in between the cholate repeat units had been found previously to enhance the folding of cholate oligomers in homogeneous solution (Zhao, Y. J. Org. Chem. 2009, 74, 834−843). The opposite effect was observed when the oligomers were solubilized in aqueous solutions of sodium dodecyl sulfate (SDS). The spacers enabled formation of tight aggregates of the oligocholates in SDS solutions when the surfactant was below its critical micelle concentration (CMC). Above the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 100 publications
0
24
0
Order By: Relevance
“…The inability of the linear trimer to move deep into the membrane is the very likely reason for its lack of transport activity and probably related to the poor packing of its intermolecular aggregate. As our previous studies revealed, loosely packed aggregates of rigid oligocholates have low stability in nonpolar environments 51,53,54 and should have difficulty moving across the membrane. …”
Section: ■ Conclusionmentioning
confidence: 90%
“…The inability of the linear trimer to move deep into the membrane is the very likely reason for its lack of transport activity and probably related to the poor packing of its intermolecular aggregate. As our previous studies revealed, loosely packed aggregates of rigid oligocholates have low stability in nonpolar environments 51,53,54 and should have difficulty moving across the membrane. …”
Section: ■ Conclusionmentioning
confidence: 90%
“…Analogously, as lacking specific secondary interactions such as the solvophobic effect to stabilize the folded conformation, oligomeric 1,8-anthrylene ethynylenes did not exhibit a stable folded conformation in solution [1,[70][71][72][73][74][75][76][77][78][79][80]. However, anthracene is known to be able to dimerize via a [4 + 4] cycloaddition, and the reaction can be reversed under suitable thermal conditions.…”
Section: Ope Oligomers End-capped With Pt Complexesmentioning
confidence: 99%
“…Since there are previously published reviews and book chapters that have comprehensively summarized earlier work on foldamers or have highlighted specific relevant topics [4,9,10,[64][65][66][67][68], the current contribution will only focus on the most recent progress related to foldamers consisting of arylene ethynylene building blocks [69][70][71][72][73][74][75][76][77][78][79][80]. Some of the work features developing novel functions based on previously established AEFS, and others have designed and synthesized new AEF structures that aim to realize previously uncharted properties.…”
Section: Introduction and Scopementioning
confidence: 99%
“…Their hydrophobicity is also evident from their surfactant-assisted solubilization in water. When fluorescently labeled oligocholates are dissolved in aqueous micellar solutions, their emission indicated their inclusion in the hydrophobic core of micelle [34][35][36].…”
Section: Design and Synthesis Of Oligocholate-peg Block Copolymersmentioning
confidence: 99%
“…These features should influence the packing of oligocholates and affect the self-assembling of the block copolymer. In a recent study, we discovered that the parent, unmodified, oligocholates pack poorly in water due to the awkward shape of the steroidal repeat unit and the short linkages between the fused aliphatic rings [36]. An interesting dichotomy thus will be created if a hydrophilic polymer is attached to an oligocholate: the large hydrophobic surface of the oligocholates demands their close packing to maximize hydrophobic interactions but such packing is difficult with the awkward shape of the repeat unit and the semirigid backbone.…”
Section: Design and Synthesis Of Oligocholate-peg Block Copolymersmentioning
confidence: 99%